PEREMPUAN DALAM KULTUR MASYARAKAT ACEH DI KABUPATEN ACEH BARAT (SUATU ANALISIS SOSIOLOGIS) - IRMA JURAIDA (Jurnal Community, 2017)
This study discusses how the existence of Women in Culture Society in West Aceh regency is known to be religious. It was formed centuries ago, so it was reflected in various aspects of life, both in behavior, social system, economic system, traditional art and so on, so habitus was formed in Aceh society. The problem in this research is how people in Aceh society culture. This research was conducted in West Aceh Regency using qualitative approach, mainly through the technique of face-prevention interview and observation. This paper is very useful to overcome social problems, culture and things that can be the background of the formation of Acehnese society culture towards women. The results of this study indicate that women in Acehnese culture are more determined by the customs, social, cultural, and values that a person or group of people in West Aceh have.  Key Words: Women, Culture, People of Aceh